Pelatihan Bahasa Inggris Bagi Remaja Panti Asuhan Melalui Jigsaw Teknik Di Panti Asuhan Siti Aisyah - Amrizal Amrizal; Rica Umrina Lubis (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This activity aims to improve teenagers’ English language ability through jigsaw techniques in Siti Aisyah Orphanage. This activity was held at the Siti Aisyah Orphanage Jalan Lintas Timur Kelurahan Dalan Lidang Kecamatan Panyabungan, and there were 6 teenagers in this activity. This activity has 8 meetings and each meeting runs for 60-90 minutes. The results of this training show that teenagers’ English language ability through jigsaw techniques in Siti Aisyah Orphanage has a satisfactory increase, namely 34.17. The pre test results were 31.66 and the post test results were 65.83 and there was an increase in participants' learning motivation as seen from the enthusiasm of participants in the learning process